Applications of the Horner–Wadsworth–Emmons Olefination in Modern Natural Product Synthesis - Roman, Dávid; Sauer, Maria; Beemelmanns, Christine (Synthesis, 2021)
The Horner–Wadsworth–Emmons (HWE) reaction is one of the most reliable olefination reaction and can be broadly applied in organic chemistry and natural product synthesis with excellent selectivity. Within the last few years HWE reaction conditions have been optimized and new reagents developed to overcome challenges in the total syntheses of natural products. This review highlights the application of HWE olefinations in total syntheses of structurally different natural products covering 2015 to 2020. Applied HWE reagents and reactions conditions are highlighted to support future synthetic approaches and serve as guideline to find the best HWE conditions for the most complicated natural products.1 Introduction and Historical Background2 Applications of HWE2.1 Cyclization by HWE Reactions2.2.1 Formation of Medium- to Larger-Sized Rings2.2.2 Formation of Small- to Medium-Sized Rings2.3 Synthesis of α,β-Unsaturated Carbonyl Groups2.4 Synthesis of Substituted C=C Bonds2.5 Late-Stage Modifications by HWE Reactions2.6 HWE Reactions on Solid Supports2.7 Synthesis of Poly-Conjugated C=C Bonds2.8 HWE-Mediated Coupling of Larger Building Blocks2.9 Miscellaneous3 Summary and Outlook
Keywords: HWE reaction; olefination; C=C bond formation; phosphonate; aldehyde; alkenes; natural products